Differential Pi3K‐pathway Activation in Cortical Tubers and Focal Cortical Dysplasias with Balloon Cells - Schick, Volker (Brain Pathol, 2007)
Balloon cells of distinct focal cortical dysplasias type IIb (FCD(IIb)) and giant cells of cortical tubers in tuberous sclerosis (TSC) constitute neuropathological hallmarks and cytological similarities. In TSC, frequent mutations in the TSC1 or TSC2 genes result in mTOR‐signaling activity. Here, we addressed whether Pi3K‐pathway activation differentiates balloon cells from giant cells. We used immunohistochemistry with antibodies against p‐PDK1 (S241), p‐Akt (S473), p‐tuberin (T1462), p‐p70(S6K) (T389), p‐p70(S6K) (T229) and phalloidin‐staining to analyze stress fiber formation in balloon cells of FCD(IIb) (n = 23) compared with cortical tuber giant cells (n = 5) and adjacent normal CNS tissue as control. We have further established an in vitro assay to assess potential phosphorylation between Akt and S6. We observed phosphorylated (p‐)PDK1, p‐Akt, p‐tuberin, and p‐p70‐kDa S6‐kinase (p‐p70(S6K); residue T229) in balloon cells, whereas giant cells showed only equivalent levels of p‐tuberin, p‐p70(S6K) and stress fibers. Furthermore, Pi3K‐cascade activity in balloon cells may reflect pathway “cross‐talk”. An in vitro assay revealed S6, a major target of p70(S6K), to increase phosphorylation of Akt. Our data suggest recruitment of different Pi3K‐cascade factors in the molecular pathogenesis of giant cells in cortical tubers vs. balloon cells in FCD(IIb) and provides new implications for the development of treatment strategies for these cortical malformations.